PUSHKIN, PERN AND POLAND: INTERPRETATION OF ONE IMPORTANT EPISODE OF MEMOIR CHRONICLE “PAST AND THOUGHTS” BY A.I. HERTZEN (Philological Studies, 2019)
In this article you can find the interpretation of one important episode from memoir Chronicles “Past and thoughts” by Alexander Herzen. Author’s meeting with the exiled Pole in Perm connects with Pushkin’s theme in literature.
Keywords: Alexander Herzen, “Past and thoughts”, interpretation of episode, images of Pushkin, Perm and Poland